FDS (Family Development Session) in The Prevention and Handling of Stunting in Lenek Pesiraman Village - Haerul Rizal Fatoni; Bintarsih Sekarningrum; Muhammad Fedryansyah (Eduvest - Journal of Universal Studies, 2025)
The issue of stunting remains a significant health concern, particularly in East Lombok, which has one of the highest stunting rates in West Nusa Tenggara. This study explores the role of Family Development Session (FDS) activities in preventing and addressing stunting in Lenek Pesiraman Village. FDS, an integral part of the Family Hope Program (PKH), provides structured learning sessions to beneficiary families (KPM) to increase their knowledge and foster behavioral changes related to health, education, and nutrition management. Using Giddens' structuration theory as an analytical tool, this research investigates the interaction between agents (beneficiary families and FDS facilitators) and structures (the PKH program) in implementing FDS activities. A qualitative case study approach was employed, with data gathered through interviews, observations, and documentation from 2019 to 2024. The findings indicate that FDS activities have significantly influenced behavioral changes in the community, particularly in improving nutrition awareness, pregnancy care, and environmental health. Additionally, FDS has facilitated a deeper understanding of stunting prevention among beneficiaries and contributed to reducing stunting rates in Lenek Pesiraman Village. The study highlights the importance of collaboration between facilitators and beneficiaries in achieving the program’s objectives and provides insights into enhancing the implementation of FDS activities for better community health outcomes